Cold-rolled steel sheet
By controlling the chemical composition and manufacturing conditions of the cold-rolled steel plate, especially the Sn content and orientation control, the problems of insufficient corrosion resistance and deep drawing properties of the cold-rolled steel plate are solved, and the corrosion resistance and deep drawing properties are improved, which is suitable for forming and processing of complex shapes.
Patent Information
- Application Number
- CN202280102387.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-09
- Publication Date
- 2025-08-08
AI Technical Summary
The existing cold-rolled steel plates have shortcomings in corrosion resistance and deep drawing properties, especially when Sn contains, the deep drawing properties fluctuate greatly and have not effectively solved this problem.
By controlling the chemical composition and manufacturing conditions of the cold-rolled steel plate, the Sn content is ensured to be between 0.020 and 0.080%, and by controlling the r value and in-plane anisotropy, a specific rL, rC, rD, mr and Δr range is adopted, and the grain ratio of the oriented {100}<001>, {111}<112> and {111}<110> is improved to improve corrosion resistance and deep drawing.
It is achieved while improving corrosion resistance, and stabilizing the deep drawing property and ensuring the formingability and yield of the cold-rolled steel plate in complex shape forming processing.
Smart Images

Figure BDA0005436003570000181 
Figure BDA0005436003570000211 
Figure BDA0005436003570000221
Abstract
Description
Technical Field
[0001] The present disclosure relates to a cold-rolled steel sheet. Background Art
[0002] Automotive parts are manufactured by stamping steel sheets, which serve as blanks. In recent years, part shapes have become increasingly diverse and complex. Consequently, cold-rolled steel sheets, used as blanks, are required to have excellent formability, particularly deep drawability. In response to these demands, for example, Patent Documents 1 and 2 disclose cold-rolled steel sheets with improved deep drawability.
[0003] Prior art literature
[0004] Patent Literature
[0005] Patent Document 1: Japanese Patent Application Laid-Open No. 2006-219737
[0006] Patent Document 2: Japanese Patent Application Laid-Open No. 2009-270191 Summary of the Invention
[0007] Problems to be solved by the invention
[0008] In recent years, in the application of the above-mentioned automotive parts, further improvement in corrosion resistance has been required for blanks due to considerations such as the use environment. However, the corrosion resistance of the cold-rolled steel sheets disclosed in Patent Documents 1 and 2 has not been fully studied. Generally, in order to improve corrosion resistance, the chemical composition of the steel sheet is adjusted. There are no reports of cold-rolled steel sheets with good deep drawability and low fluctuation in deep drawability, even in cold-rolled steel sheets containing a certain amount of Sn.
[0009] In view of the above, an object of the present disclosure is to solve the above-mentioned problems and provide a cold-rolled steel sheet containing a certain amount of Sn or more in order to improve corrosion resistance and having improved deep drawability.
[0010] Solutions for solving problems
[0011] The present disclosure has been made to solve the above-mentioned problems, and is mainly based on the following cold-rolled steel sheet.
[0012] (1) A cold-rolled steel sheet having a chemical composition in mass % of
[0013] C: 0.0005~0.0070%,
[0014] Si: 0.01-1.50%,
[0015] Mn: 0.05-1.50%,
[0016] P: 0.001~0.150%,
[0017] S: 0.0005~0.0100%,
[0018] Al: 0.005~0.100%,
[0019] N: 0.0010~0.0200%,
[0020] Ti: 0.010~0.150%,
[0021] Sn: 0.020~0.080%,
[0022] Nb: 0~0.060%,
[0023] B: 0~0.0030%,
[0024] Mo: 0~0.50%,
[0025] Cr: 0-3.00%,
[0026] W: 0~3.00%,
[0027] Cu: 0-3.00%,
[0028] Ni: 0-3.00%,
[0029] Ca: 0~0.1000%,
[0030] REM: 0~0.100%
[0031] V: 0~0.10%
[0032] As: 0~0.10%,
[0033] Sb: 0-0.10%,
[0034] Pb: 0~0.10%,
[0035] Bi: 0~0.10%,
[0036] Balance: Fe and impurities,
[0037] The cold-rolled steel sheet satisfies the following equations (i) and (ii):
[0038] rL, which is the r value in the rolling direction, is 1.50 or more.
[0039] rC, which is the r value in the direction perpendicular to the rolling direction, is 1.50 or more.
[0040] rD, which is the r value in the direction at 45° to the rolling direction, is 1.50 or more.
[0041] mr defined by the following formula (iii) is 1.70 or more,
[0042] Δr defined by the following formula (iv) is in the range of -0.40 to 0.40,
[0043] Ti-48 / 32×S-48 / 14×N-48 / 12×C≥-0.010· · · (i)
[0044] 5.0≤11Si+33Mn+21Mo+17(Cr+Cu+Ni)-30Al≤50.0· · · (ii)
[0045] mr=(rL+2rD+rC) / 4· · · (iii)
[0046] Δr=(rL+rC-2rD) / 2···(iv)
[0047] The symbols of the elements in the formulas (i) and (ii) above represent the content (mass %) of the elements contained in the steel, and when the elements are not contained, the content is set to 0%.
[0048] (2) The cold-rolled steel sheet according to (1) above, wherein
[0049] In the cold-rolled steel sheet,
[0050] The random intensity ratio (A) which is the random intensity ratio of the {100}<001> orientation is 1.8 or less,
[0051] The random intensity ratio (B), which is the random intensity ratio of the {111}<112> orientation, is 4.0 or more,
[0052] The random intensity ratio (C) as the random intensity ratio of the {111}<110> orientation is 4.0 or greater, and the ratio of the random intensity ratio (B) to the random intensity ratio (C) satisfies the following formula (v), 0.80≤random intensity ratio (B) / random intensity ratio (C)≤1.20···(v).
[0053] (3) The cold-rolled steel sheet according to (1) or (2), wherein:
[0054] The chemical composition contains, in mass%,
[0055] Nb: 0.001~0.060%,
[0056] B: 0.0001~0.0030%,
[0057] Mo: 0.01~0.50%,
[0058] Cr: 0.01~3.00%,
[0059] W: 0.01~3.00%,
[0060] Cu: 0.01~3.00%,
[0061] Ni: 0.01~3.00%,
[0062] Ca: 0.0001~0.1000%,
[0063] REM: 0.001~0.100%,
[0064] V: 0.01~0.10%,
[0065] As: 0.01~0.10%,
[0066] Sb: 0.01~0.10%,
[0067] Pb: 0.01~0.10%, and
[0068] Bi: 0.01 to 0.10% of one or more kinds of Bi.
[0069] Effects of the Invention
[0070] According to the present disclosure, it is possible to obtain a cold-rolled steel sheet that contains Sn in a certain amount or more in order to improve corrosion resistance and has improved deep drawability. BRIEF DESCRIPTION OF THE DRAWINGS
[0071] Figure 1 It means in Plot of the main orientations on the ODF of the cross section. DETAILED DESCRIPTION
[0072] The present inventors conducted various studies to obtain a cold-rolled steel sheet having good deep drawability while containing a certain amount of Sn to improve corrosion resistance, and obtained the following findings (a) to (c).
[0073] (a) Sn is a relatively inexpensive element and is widely used to improve corrosion resistance. Furthermore, in order to improve corrosion resistance, it is particularly effective to set the Sn content to 0.020% or more in the chemical composition of the steel sheet.
[0074] (b) Here, in order to improve deep drawability, the r value, which is an indicator of formability, is increased, and further, the in-plane anisotropy needs to be reduced. In-plane anisotropy means that when plastic deformation occurs, the difficulty of deformation varies in the same plane due to different directions. If the in-plane anisotropy is large, uniform forming cannot be performed, and it is difficult to form a complex shape. As a result, the yield rate is likely to decrease. As the Sn content increases, the absolute value of the r value decreases, and the in-plane anisotropy increases. In particular, the inventors found that this tendency is significant when the Sn content is 0.020% or more, and the deep drawability decreases.
[0075] (c) The present inventors have studied the mechanism by which the presence of Sn at 0.020% or more adversely affects deep drawability. It is speculated that this is because a transition zone, which serves as a nucleation site for recrystallization, is formed in the {100}<001>-oriented grains, and the {100}<001> orientation and its vicinity are easily developed during annealing. Therefore, in order to improve hardenability and reduce the number of {100}<001>-oriented grains at the end of hot rolling, it was found that controlling various hot rolling manufacturing conditions (specifically, a reduction ratio of 950°C or less, the rolled shape ratio of the final pass and the rolled shape ratio of the pass immediately before the final pass, and the time from the end of hot rolling to the start of cooling) is effective.
[0076] Furthermore, it is speculated that by developing grains with a {111}<112> orientation and grains with a {111}<110> orientation, which increase the r value, and controlling the grain ratio of these two orientations, in-plane anisotropy can be improved. Therefore, controlling the cold rolling rate and the subsequent annealing temperature was also found to be effective. Based on the above, the inventors have determined that such microstructure control suppresses the reduction of the r value and the increase of in-plane anisotropy.
[0077] An embodiment of the present disclosure is made based on the above-mentioned findings. Hereinafter, each element of the embodiment will be described in detail.
[0078] 1. Chemical composition
[0079] The reasons for limiting the content of each element are as follows: In the following description, "%" for the content means "mass %".
[0080] C: 0.0005~0.0070%
[0081] C has the effect of increasing strength. Furthermore, containing a certain amount of C increases the r-value and reduces in-plane anisotropy. Therefore, the C content is set to 0.0005% or more. The C content is preferably set to 0.0007% or more, 0.0010% or more, or 0.0015% or more. However, excessive C content decreases the r-value. Therefore, the C content is set to 0.0070% or less. The C content is preferably set to less than 0.0050%, 0.0040% or less, or 0.0030% or less.
[0082] Si: 0.01~1.50%
[0083] Si is a deoxidizing element. In addition, Si is an element that improves strength by solid solution strengthening. Therefore, the Si content is set to 0.01% or more. The Si content is preferably set to 0.03% or more, 0.05% or more, or 0.10% or more. However, if the Si content is greater than 1.50%, the stamping formability is reduced, or the chemical conversion treatability is reduced. Therefore, the Si content is set to 1.50% or less. In the case of hot-dip galvanizing, problems such as a decrease in coating adhesion and a decrease in productivity due to a delay in the alloying reaction arise. Therefore, the Si content is preferably set to 1.20% or less, 1.00% or less, 0.80% or less, 0.65% or less, 0.50% or less, or 0.35% or less.
[0084] Mn: 0.05~1.50%
[0085] Mn has the effect of improving strength as a solid solution strengthening element, therefore, a certain amount of Mn is contained according to the application. In addition, setting the Mn content to less than 0.05% not only fails to obtain special effects in terms of characteristics, but also increases the cost of steelmaking, therefore, the Mn content is set to 0.05% or more. From this viewpoint, the Mn content is preferably set to more than 0.10%, more than 0.20%, or more than 0.30%. However, if Mn is contained excessively, the strength becomes too high, therefore, the r value decreases, or the adhesion of galvanizing is hindered. Therefore, the Mn content is preferably set to less than 1.50%, less than 1.20%, less than 1.00%, or less than 0.90%.
[0086] P: 0.001~0.150%
[0087] P is an impurity contained in steel. Like Si, it can improve strength at a low cost. In addition, P also has the effect of making the hot-rolled structure fine and improving deep drawability. Therefore, the P content is set to 0.001% or more. The P content is preferably set to 0.005% or more, 0.0010% or more, 0.0015% or more, or 0.0020% or more. However, if P is contained excessively, the fatigue strength after spot welding is poor, or the yield strength is excessively increased, causing poor surface shape during stamping. Moreover, the alloying reaction is extremely slow during continuous hot-dip galvanizing, and productivity is reduced. In addition, secondary workability is also reduced. Therefore, the P content is set to 0.150% or less. The P content is preferably set to 0.100% or less, 0.080% or less, 0.050% or less, 0.030% or less, or 0.020% or less.
[0088] S: 0.0005~0.0100%
[0089] S is an impurity contained in steel. If the S content exceeds 0.0100%, hot cracking and deep drawability are more likely to occur. Therefore, the S content is set to 0.0100% or less. The S content is preferably set to 0.0090% or less, 0.0070% or less, or 0.0050% or less. The S content is preferably minimized; excessive reduction increases manufacturing costs. Therefore, the S content is set to 0.0005% or more. The S content is preferably set to 0.0010% or more.
[0090] Al: 0.005~0.100%
[0091] Al is an element used as a deoxidation modulator. Furthermore, Al significantly increases the phase transition point and therefore also has the effect of adjusting the phase transition point. Therefore, the Al content is set to 0.005% or more. The Al content is preferably set to 0.010% or more, 0.0015% or more, or 0.0020% or more. However, even if Al is contained in excess, not only will the aforementioned effects be saturated, but nitrides may also be formed, lowering the r value. Therefore, the Al content is set to 0.100% or less. The Al content is preferably set to 0.080% or less, 0.0060% or less, or 0.0050% or less.
[0092] N: 0.0010~0.0200%
[0093] Nitrogen is an impurity contained in steel. If the N content is less than 0.0010%, steelmaking costs increase. Therefore, the N content is set to 0.0010% or higher. The N content is preferably set to 0.0015% or higher, 0.0020% or higher, or 0.0025% or higher. However, excessive N content leads to excessive nitride formation, reducing the r value. Therefore, the N content is set to 0.0200% or lower. The N content is preferably set to 0.0150% or lower, 0.0100% or lower, or 0.0080% or lower.
[0094] Ti: 0.010~0.150%
[0095] Ti has the effect of reducing solid-solution C by forming carbides, and also of making the grains of the hot-rolled steel sheet finer, thereby increasing the r-value. Therefore, the Ti content is set to 0.010% or more. The Ti content is preferably set to 0.020% or more, or 0.025% or more. In addition, in the steel sheet of this embodiment, the manufacturing cost increases, so the Ti content is reduced. In addition, if Ti is contained excessively, the r-value decreases. Therefore, the Ti content is set to 0.150% or less. The Ti content is preferably set to 0.100% or less, 0.080% or less, less than 0.070%, or less than 0.050%.
[0096] Sn: 0.020~0.080%
[0097] Sn has the effect of improving corrosion resistance. Therefore, the Sn content is set to 0.020% or more. As the Sn content increases, the corrosion resistance improves, so it is preferably set to 0.025% or more, and more preferably set to 0.030% or more. However, Sn is an element that reduces the r value and increases its in-plane anisotropy. Therefore, if Sn is contained excessively, the above-mentioned characteristics will be significantly reduced even if the manufacturing conditions are controlled. Therefore, the Sn content is set to 0.080% or less. The Sn content is preferably set to 0.070% or less, 0.060% or less, or 0.050% or less.
[0098] In addition to the above elements, one or more selected from Nb, B, Mo, Cr, W, Cu, Ni, Ca, REM, V, As, Sb, Pb, and Bi may be contained within the ranges shown below. The reasons for limiting each element are explained below. The inclusion of these elements is not essential, and their lower limits are all 0%.
[0099] Nb: 0~0.060%
[0100] Nb has the effect of refining the grains of hot-rolled steel sheets and increasing the r-value. Therefore, it may be contained as needed. However, excessive Nb significantly inhibits recrystallization, so the Nb content is set to 0.060% or less. The Nb content is more preferably set to 0.040% or less, or 0.020% or less. On the other hand, to achieve the above-mentioned effects, the Nb content is preferably set to 0.001% or more, and more preferably to 0.005% or more.
[0101] B: 0~0.0030%
[0102] Boron strengthens grain boundaries. It also increases the strength of the steel sheet. Therefore, it may be contained as needed. However, excessive B content can lead to excessive increases in strength, decreases in r-value, and thus reduced deep drawability. Therefore, the B content is set to 0.0030% or less. The B content is preferably set to 0.0020% or less, or 0.0015% or less. On the other hand, to achieve the aforementioned effects, the B content is preferably set to 0.0001% or more, and more preferably 0.0002% or more.
[0103] Mo: 0~0.50%
[0104] In the steel sheet of this embodiment, it is necessary to suppress the reduction in r-value caused by the inclusion of Sn. It is believed that if grains with a {100}<001> orientation remain during the hot-rolled steel sheet, the formation of a deformed structure known as a transition zone is promoted, leading to the aforementioned reduction in r-value. Therefore, it is necessary to develop grains with orientations other than {100}<001>, such as {100}<011>, {211}<011>, and {332}<113>, during the hot-rolled steel sheet.
[0105] Here, Mo suppresses the formation of a transition zone by improving hardenability, developing the transformation texture of the hot-rolled steel sheet, and suppressing the development of {100}<001> oriented grains. As a result, it has the effect of increasing the r value. Therefore, it can be contained as needed. However, if Mo is contained in excess, the r value will decrease and the deep drawability will decrease. Therefore, the Mo content is set to 0.50% or less. The Mo content is preferably set to 0.30% or less, or 0.20% or less. On the other hand, in order to obtain the above-mentioned effects, the Mo content is preferably set to 0.01% or more.
[0106] Cr: 0~3.00%
[0107] Cr, like Mo, has the effect of increasing the r-value by improving hardenability and developing the phase transformation texture of the hot-rolled steel sheet. Therefore, it can be contained as needed. However, if Cr is contained in excess, the manufacturing cost increases. Therefore, the Cr content is set to 3.00% or less. The Cr content is preferably set to 2.50% or less, 2.00% or less, 1.50% or less, or 1.00% or less. On the other hand, to achieve the above-mentioned effects, the Cr content is preferably set to 0.01% or more, and more preferably set to 0.03% or more.
[0108] W: 0~3.00%
[0109] W has the effect of improving strength. Therefore, it may be contained as needed. However, excessive W content increases manufacturing costs. Therefore, the W content is set to 3.00% or less. The W content is preferably set to 2.50% or less, 2.00% or less, 1.50% or less, 1.00% or less, 0.50% or less, 0.10% or less, or 0.05% or less. On the other hand, to achieve the above-mentioned effects, the W content is more preferably set to 0.01% or more.
[0110] Cu: 0-3.00%
[0111] Cu, like Mo, has the effect of improving the r-value by improving the hardenability and developing the phase transformation texture of the hot-rolled steel sheet. Therefore, it can also be contained as needed. However, if Cu is contained excessively, the manufacturing cost increases. Therefore, the Cu content is set to 3.00% or less. The Cu content is preferably set to 2.50% or less, 2.00% or less, 1.50% or less, 1.00% or less, 0.50% or less, or 0.30% or less. On the other hand, in order to obtain the above-mentioned effects, the Cu content is preferably set to 0.01% or more.
[0112] Ni: 0-3.00%
[0113] Like Mo, Ni also has the effect of improving the r-value by improving the hardenability and developing the phase transformation texture of the hot-rolled steel sheet. Therefore, it can also be contained as needed. However, if Ni is contained excessively, the manufacturing cost increases. Therefore, the Ni content is set to 3.00% or less. The Ni content is preferably set to 2.50% or less, 2.00% or less, 1.50% or less, 1.00% or less, 0.50% or less, or 0.25% or less. On the other hand, in order to obtain the above-mentioned effects, the Ni content is preferably set to 0.01% or more.
[0114] Ca: 0~0.1000%
[0115] In addition to being useful as a deoxidizing element, Ca also has the effect of controlling the morphology of sulfides. Therefore, it may be contained as needed. However, excessive Ca content increases manufacturing costs. Therefore, the Ca content is set to 0.1000% or less. The Ca content is preferably set to 0.0500% or less, 0.0300% or less, 0.0150% or less, 0.0075% or less, or 0.0030% or less. On the other hand, to achieve the above-mentioned effects, the Ca content is preferably set to 0.0001% or more, and more preferably 0.0005% or more.
[0116] REM: 0~0.100%
[0117] REM has the effect of improving strength. Therefore, it can be contained as needed. However, if REM is contained in excess, this effect is saturated, and manufacturing costs increase. Therefore, the REM content is set to 0.100% or less. The REM content is preferably set to 0.080% or less, 0.060% or less, 0.040% or less, 0.020% or less, 0.010% or less, or 0.005% or less. On the other hand, to achieve the above-mentioned effects, the REM content is preferably set to 0.001% or more.
[0118] REM refers to a total of 17 elements including Sc, Y, and lanthanoids, and the above REM content means the total content of these elements. REM is often added in the form of mixed rare earth in industry.
[0119] V: 0~0.10%
[0120] V has the effect of refining the grains of hot-rolled steel sheets. Therefore, it may be contained as needed. However, excessive V content excessively inhibits recrystallization, so the V content is set to 0.10% or less. The V content is preferably set to 0.08% or less, 0.06% or less, or 0.04% or less. On the other hand, to achieve the above-mentioned effects, the V content is preferably set to 0.01% or more.
[0121] As: 0~0.10%
[0122] Sb: 0~0.10%
[0123] Pb: 0~0.10%
[0124] Bi: 0~0.10%
[0125] As, Sb, Pb, and Bi are elements that may be present as impurities. These elements should be minimized, as they may be present in the steel depending on the raw materials. Therefore, the As content should be set to 0.10% or less. Furthermore, the Sb content should be set to 0.10% or less. The Pb content should be set to 0.10% or less. The Bi content should be set to 0.10% or less. These elements should be minimized, and the total content of these elements should preferably be set to 0.40% or less. The lower limit of these elements may also be set to 0.01%.
[0126] In the chemical composition of this embodiment, the balance is Fe and Fe is impurities. Here, "impurities" refer to components that are mixed into the steel sheet during industrial production due to various factors such as raw materials such as ore and scrap, and the manufacturing process, and are acceptable components that do not adversely affect this embodiment.
[0127] (i)Formula
[0128] Here, the chemical composition satisfies the following formula (i).
[0129] Ti-48 / 32×S-48 / 14×N-48 / 12×C≥-0.010···(i)
[0130] In the above formula (i), each element symbol represents the content (mass %) of each element contained in the steel, and when not contained, it is set to 0%.
[0131] The value on the left side of the above formula (i) is used to express the value obtained by subtracting the amount of Ti precipitated as Ti sulfide, Ti nitride, and Ti carbide from the Ti content, and becomes an indicator of the amount of solid-solution Ti. By controlling the amount of solid-solution Ti within an appropriate range, the amount of solid-solution C in the hot-rolled steel plate can be reduced, and the r value can be improved. Therefore, in the steel plate of this embodiment, while minimizing Ti, the above-mentioned effect can still be obtained. Therefore, the value on the left side of the formula (i) is set to -0.010 (unit is mass %. Similarly, the unit description is omitted below.) or above, preferably set to 0.010 or above, and preferably set to 0.013 or above. In addition, the upper limit value of the value on the left side of the formula (i) is not particularly limited. However, when the value on the left side of the formula (i) is calculated from the range of the content of each element in the steel plate of this embodiment, 0.143 becomes the upper limit value. In addition, the above formula (i) is a formula derived through experiments.
[0132] Formula (ii)
[0133] Here, the chemical composition satisfies the following formula (ii).
[0134] 5.0≤11Si+33Mn+21Mo+17(Cr+Cu+Ni)-30Al≤50.0···(ii)
[0135] In the above formula (ii), each element symbol represents the content (mass %) of each element contained in the steel, and when no element is contained, it is set to 0%.
[0136] The above formula (ii) is an indicator of the hardenability after hot rolling and is a formula derived through experiments. In addition, if the intermediate value of formula (ii) is less than 5.0 (the unit is mass %. Similarly, the unit description is omitted below.), sufficient hardenability cannot be ensured and the texture of the hot-rolled steel sheet does not develop. As a result, it is believed that: {100}<001> orientation remains in the hot-rolled steel sheet, and the reduction of r value caused by Sn cannot be suppressed, and its in-plane anisotropy also becomes larger. Therefore, the intermediate value of formula (ii) is set to 5.0 or more. The intermediate value of formula (ii) is preferably set to 7.0 or more, and more preferably set to 9.0 or more. On the other hand, if the intermediate value of formula (ii) is greater than 50.0, the reduction effect of {100}<001> orientation is not only saturated, but also recovery and recrystallization are significantly delayed. As a result, the r value decreases. Therefore, the intermediate value of formula (ii) is set to 50.0 or less. The intermediate value of formula (ii) is preferably set to 40.0 or less.
[0137] 2. r value
[0138] 2-1. r value in each direction
[0139] In the steel plate of this embodiment, rL, which is the r value in the rolling direction, rC, which is the r value in the direction perpendicular to the rolling direction, and rD, which is the r value in the direction at 45° to the rolling direction, are set to the following ranges.
[0140] Specifically, rL, the r value in the rolling direction, is set to 1.50 or greater. This is because if rL is less than 1.50, good deep drawability cannot be achieved. rL is preferably set to 1.60 or greater, and more preferably to 1.70 or greater. The upper limit of rL is not particularly limited, but is generally around 3.00.
[0141] rC, which is the r value in the direction perpendicular to the rolling direction, is also set to 1.50 or greater. This is because if rC is less than 1.50, good deep drawability cannot be achieved. rC is preferably set to 1.60 or greater, and more preferably set to 1.70 or greater. The upper limit of rC is not particularly limited, but is generally around 3.00.
[0142] rD, which is the r value in the direction 45° to the rolling direction, is also set to 1.50 or greater. This is because if rD is less than 1.50, good deep drawability cannot be achieved. rD is preferably set to 1.60 or greater, and more preferably to 1.70 or greater. The upper limit of rD is not particularly limited, but is generally around 3.00.
[0143] In addition, the various r values (rL, rD, rC) mentioned above are measured by performing a tensile test in accordance with 3.1 of JIS Z 2254:2021. In addition, during the test, a strain is applied by applying a tensile elongation of 15.0±1.0% (total elongation), and after removing the strain, the length between the measurement points is measured. However, according to Note 3 of 3.1 of JIS Z 2254:2021, the r value is calculated using the formula (2) of the above Note 3 using the measurement result of the length (instead of the thickness measurement). In the tensile test, three test pieces are used in one direction, and the average value thereof is set as the r value in each direction.
[0144] Three types of test specimens were prepared: those with the rolling direction as the longitudinal direction, those with the longitudinal direction perpendicular to the rolling direction, and those with the longitudinal direction at a 45° angle to the rolling direction. The test specimens were shaped like JIS Z 2241:2022 No. 5 test specimens, with the distance between the markings on the parallel portion set to 20 mm. A predetermined number of test specimens were collected from a predetermined distance near the center of the steel plate width where the average characteristic value was obtained, so as not to be affected by processing during collection.
[0145] In order to measure the above-mentioned r value, it is necessary to determine the rolling direction. For example, when the steel plate is in the shape of a coil, the longitudinal direction of the coil (coiling direction) becomes the rolling direction. On the other hand, in the case of the cut plate, the rolling direction is determined in the following order. First, when a stripe pattern can be identified on the surface of the cut plate (steel plate), the direction parallel to the stripe pattern is set as the rolling direction. On the other hand, when the stripe pattern cannot be identified, an arbitrary thickness section of the cut plate is assumed to be a section perpendicular to the width direction during rolling and a measurement based on EBSD (Electron BackScattering Diffraction) is performed. In the cross section, an ODF (Orientation Distribution Function) is prepared. This series of measurement and analysis procedures are the same as the measurement and analysis procedures for the random intensity ratio described later.
[0146] Confirm whether the end of the cut plate is parallel or perpendicular to the rolling direction. In case the end of the cut plate is not parallel or perpendicular to the rolling direction, or The sum of the random intensity ratios of Φ=0~45° except Φ=Sum of random intensity ratios from 0 to 45° (A) or The sum of the random intensity ratios (B) for Φ = 0 to 45° is large. In this case, the random intensity ratio is measured by slightly shifting the acquisition direction of the cross section to find or The direction in which the sum of the random intensity ratios is the largest is the direction parallel to or perpendicular to the rolling direction. Therefore, a cross section parallel to or perpendicular to the rolling direction can be determined.
[0147] In cross sections parallel to or perpendicular to the rolling direction, the random intensity ratio (A) is compared with the random intensity ratio (B). If (A) > (B), the cross section measured is perpendicular to the rolling width direction. If (A) < (B), the cross section measured is perpendicular to the rolling direction. Thus, by determining the cross section, the rolling direction can also be determined. Furthermore, the sum of the random intensity ratios is calculated for every 5°, using Φ = 0, 5, 10, etc., and then summed.
[0148] 2-2. Average r value
[0149] In the steel plate of the present embodiment, mr (average r value) defined by the following formula (iii) is set to 1.70 or more.
[0150] mr=(rL+2rD+rC) / 4···(iii)
[0151] As described above, each symbol in the above formula (iii) is defined as follows.
[0152] rL: r value in rolling direction
[0153] rD: r value at 45° to the rolling direction
[0154] rC: r value in the direction perpendicular to the rolling direction
[0155] mr is also called the average plastic strain ratio. The larger its value, the better the deep drawability. If mr is less than 1.70, good deep drawability cannot be obtained. Therefore, mr is set to 1.70 or more, and more preferably set to 1.80 or more. In addition, the upper limit of mr is not particularly limited, and is generally about 3.00.
[0156] 2-3.Δr
[0157] In the steel sheet of the present embodiment, Δr, which is an index of in-plane anisotropy and is defined by the following formula (iv), is set in the range of -0.40 to 0.40.
[0158] Δr=(rL+rC-2rD) / 2···(iv)
[0159] As described above, each symbol in the above formula (iv) is defined as follows.
[0160] rL: r value in rolling direction
[0161] rD: r value at 45° to the rolling direction
[0162] rC: r value in the direction perpendicular to the rolling direction
[0163] It is desirable that the closer Δr is to 0, the smaller the in-plane anisotropy. However, in the steel sheet of this embodiment, if Δr is less than -0.40, the in-plane anisotropy is large, and good deep drawability cannot be achieved. Therefore, Δr is set to be greater than -0.40, preferably greater than -0.35, greater than -0.30, or greater than -0.25. On the other hand, even if Δr is greater than 0.40, the in-plane anisotropy is large, and good deep drawability cannot be achieved. Therefore, Δr is set to be less than 0.40, preferably less than 0.35, less than 0.30, or less than 0.25. In other words, |Δr|, the absolute value of Δr, is set to be less than 0.40. |Δr| is more preferably less than 0.35, less than 0.30, or less than 0.25.
[0164] 3. Random intensity ratio
[0165] In the steel sheet of this embodiment, as described above, it is desirable to reduce the number of {100}<001> oriented grains, which contribute to a decrease in the r-value. Therefore, the random intensity ratio (A), which is the random intensity ratio of the {100}<001> orientation, is preferably set to 1.8 or less, and more preferably to 1.6 or less or 1.5 or less.
[0166] Furthermore, it is desirable to develop grains of the γ-fiber texture (γ-fiber), which has the effect of increasing the r-value, in an appropriate range, that is, grains having a {111} orientation on the plate surface. Therefore, the random intensity ratio (B), which is the random intensity ratio of the {111}<112> orientation, is preferably set to 4.0 or greater, more preferably 4.5 or greater or 5.0 or greater. Similarly, the random intensity ratio (C), which is the random intensity ratio of the {111}<110> orientation, is preferably set to 4.0 or greater, more preferably 4.5 or greater or 5.0 or greater.
[0167] On the other hand, if the γ-fiber texture develops excessively, the in-plane anisotropy increases. Among the orientation groups of the γ-fiber texture, grains with a {111}<112> orientation also preferentially grow during annealing. Therefore, in order to achieve a well-balanced growth with both the r value and in-plane anisotropy, it is necessary to grow not only grains with a {111}<112> orientation but also grains with other {111} orientations. Therefore, the ratio of the random intensity ratio (B) to the random intensity ratio (C), that is, the ratio of the random intensity ratio (B) to the random intensity ratio (C), preferably satisfies the following equation (v).
[0168] 0.80≤Random intensity ratio (B) / Random intensity ratio (C)≤1.20···(v)
[0169] If the ratio of the random intensity ratio (B) to the random intensity ratio (C), which is the intermediate value of formula (v), is less than 0.80, the growth of grains with an orientation group having a γ-fiber texture is not well-balanced, and the r value tends to decrease. Therefore, the intermediate value of formula (v) is preferably 0.80 or greater, and more preferably 0.85 or greater or 0.90 or greater.
[0170] Similarly, if the median value of formula (v) exceeds 1.20, the growth of grains with a γ-fiber texture is not well-balanced, resulting in a structure with excessive development of {111}<112>-oriented grains. As a result, the in-plane anisotropy increases. Therefore, the median value of formula (v) is preferably 1.20 or less, and more preferably 1.15 or less, or 1.10 or less.
[0171] Various random intensity ratios (random intensity ratio (A), random intensity ratio (B), and random intensity ratio (C)) were measured in the following order. Specifically, the random intensity ratios were generated based on the crystal orientation data obtained by EBSD measurement. The concentration of each crystal orientation on the cross-sectional ODF was calculated. The measurement was performed on a cross section perpendicular to the rolling width direction, but the crystal orientation data obtained on the cross section was converted into data perpendicular to the sheet surface to determine the ODF.
[0172] ODF is also used to represent the orientation of crystal structures with low symmetry, so it is generally used as Φ=0~180°、 Each orientation is represented by (hkl)[uvw]. However, in the steel plate of this embodiment, the bcc crystal structure with high symmetry is the target, so for Φ and Expressed in the range of 0 to 90°.
[0173] In addition, for The range varies depending on whether the symmetry due to deformation is considered during calculation. However, in the steel plate of this embodiment, the symmetry due to rolling deformation is considered. Mark. Figure 1 in The main orientation is shown on the ODF of the cross section. Figure 1 In the example, (111)[1-10] and (111)[0-11] are equivalent, and it is agreed that they are all {111}<110> as a mark considering symmetry. Therefore, any random intensity ratio becomes the same value, but in the steel plate of this embodiment, The value of Φ=55° is used as the random intensity ratio of {111}<110>. Similarly, {100}<001> is set as Φ=0°,{111}<112>is set to The value of Φ = 55°.
[0174] In addition, in ODF, for example, the {100}<001> orientation strictly refers to the In the cross section However, sometimes measurement errors may occur due to the processing of the test piece and the setting of the sample. The maximum value in the range of Φ = 0 to 5° represents the random intensity of the orientation. The random intensity ratio is measured with an error of ±5° allowed for each axis of Φ. Similarly, in other orientations, The measurement was performed with an error of 5° allowed for each axis of Φ.
[0175] When generating the ODF, analysis was performed under the following conditions using "OIM Analysis," which is analysis software manufactured by TSL Corporation.
[0176] Calculation method: Harmonic series expansion method
[0177] Series order [L]: 16
[0178] Gaussian half width [degrees]: 5
[0179] Sample symmetry: orthotropic (rolled steel plate)
[0180] In EBSD measurements, the steel plate is mechanically or chemically polished, and a cross section perpendicular to the plate width is polished to a mirror finish. Then, strain is removed by electrolytic or chemical polishing to prepare a test piece. The measurement range is the entire thickness in the plate thickness direction and 1 mm in the rolling direction. The measurement interval is not particularly limited; it is preferably adjusted to a maximum of 10,000 measurement points.
[0181] Furthermore, while microstructure analysis was performed using various methods on the steel sheet of the present embodiment (the inventive cold-rolled steel sheet) and steel sheets that did not meet the target values for deep drawing (r value, mr value, Δr value in each direction), the characteristics of the microstructure that characterizes the steel sheet of the present embodiment could not be clearly identified. However, even for steel sheets that met the requirements for the random strength ratio, it was confirmed that steel sheets that did not meet the target values for deep drawing were found, but it was confirmed that at least the steel sheet of the present embodiment met the requirements for the random strength ratio.
[0182] 4. Tensile strength
[0183] In the steel sheet of this embodiment, the tensile strength (also referred to as "TS") is preferably set to the range of 270 to 450 MPa. This is because if the TS is less than 270 MPa, the desired strength cannot be obtained, while if the TS is greater than 450 MPa, not only deep drawability but also formability is reduced.
[0184] 5. Plating
[0185] The steel sheet of this embodiment may also have a coating on its surface as needed. The coating is preferably an electroplated layer, a hot-dip galvanized layer, or an alloyed hot-dip galvanized layer. Furthermore, an electroplated layer refers to a coating formed by electroplating. A hot-dip galvanized layer refers to a coating formed by immersing the steel sheet in molten zinc at a high temperature. An alloyed hot-dip galvanized layer refers to a coating formed by heat-treating a hot-dip galvanized steel sheet to form an iron-zinc alloy.
[0186] 6. Manufacturing Method
[0187] A preferred method for producing the steel sheet according to the present embodiment will be described. The steel sheet according to the present embodiment can be produced stably by the following production method.
[0188] Slabs are produced by melting and casting steel having the above-mentioned chemical composition using conventional methods. Slabs can be continuous casting slabs or billets produced using a thin slab continuous caster or the like. Alternatively, they can be produced using a continuous casting-direct rolling (CC-DR) process, where hot rolling is performed immediately after casting.
[0189] The resulting slab is hot-rolled to form a hot-rolled steel sheet. The slab heating temperature during hot rolling is not particularly limited, but is typically set within the range of 1150-1350°C. If the slab heating temperature is lower than 1150°C, carbides and other substances will not be fully melted. On the other hand, if the slab heating temperature exceeds 1350°C, the grains will coarsen. This also increases the energy required for production, leading to higher production costs.
[0190] During hot rolling, shear deformation occurs in the surface layer of a hot-rolled steel sheet due to friction between the rolls and the steel sheet, causing the development of crystal orientations different from those in the center of the sheet thickness. This includes the {100}<001> orientation, which is the primary cause of the transition zone. Therefore, minimizing the shear deformation layer is desirable.
[0191] Hot rolling typically involves two rolling processes: rough rolling and finishing rolling, which is performed after rough rolling. In each rolling process, multiple rolling mills with a pair of rolls are installed in series. Steel plates are rolled by passing between the rolling mills of these multiple rolling mills. The passage of a steel plate between the roll pairs of a rolling mill is referred to as a pass. Therefore, during rough rolling or finishing rolling, the target plate thickness is achieved through multiple passes.
[0192] The higher the rolling shape ratio in the final pass of finishing rolling (hereinafter also referred to as the "final pass") and the previous pass (hereinafter also referred to as the "previous pass"), the more developed the above-mentioned shear deformation layer is. Therefore, the rolling shape ratio of the final pass of finishing rolling is set to 3.3 or less, and the rolling shape ratio of the previous pass is set to 3.6 or less. In addition, the rolling shape ratio is defined by the following formula (a). In addition, the symbols in formula (a) are defined as follows.
[0193] Γ=ld / hm···(a)
[0194] However, the symbols in the above formula (a) are defined as follows.
[0195] Γ: Rolling shape ratio
[0196] ld: Projected contact arc length
[0197] hm: average plate thickness
[0198] In addition, the above-mentioned ld and hm are calculated from the following formulas (b) and (c).
[0199]
[0200] hm=(H+2h) / 3···(b)
[0201] The symbols in the above formula (b) are defined as follows.
[0202] R: roller radius
[0203] H: Entry thickness (the thickness of the plate before entering the rolling mill of this pass)
[0204] h: Outgoing plate thickness (plate thickness when exiting the rolling mill at this pass)
[0205] In addition, the finishing temperature (hereinafter also referred to as "FT") is set in the range of 880 to 950°C. If FT is less than 880°C, the surface layer becomes hot rolled in the α region. As a result, there is a possibility that the {110} plane-oriented grains that increase the anisotropy of the r value remain after annealing after cold rolling. Therefore, it is difficult to reduce the in-plane anisotropy. In addition, as a result of the reduction of various r values, there is a case where mr is reduced. Therefore, FT is set to 880°C or above. On the other hand, if FT is greater than 950°C, the grains become coarse, and there is a case where various r values and mr are reduced. Therefore, FT is set to 950°C or below.
[0206] Here, during hot rolling, the reduction ratio in the temperature range of 980°C or below is set to a range of 35% to 55%. If the reduction ratio in the temperature range of 980°C or below is less than 35%, various r values tend to decrease. As a result, mr may decrease. Therefore, the reduction ratio in the temperature range of 980°C or below is set to 35% or above. On the other hand, if the reduction ratio in the temperature range of 980°C or below is greater than 55%, mr decreases and becomes less than 1.70. Therefore, the reduction ratio in the temperature range of 980°C or below is set to 55% or below.
[0207] After hot rolling, the hot-rolled steel sheet is cooled. Cooling should begin within 0.5 seconds after hot rolling is complete. If the time from hot rolling to the start of cooling exceeds 0.5 seconds, the overall r value tends to decrease, resulting in mr less than 1.70. Therefore, the time from hot rolling to the start of cooling should be within 0.5 seconds.
[0208] After hot rolling, the hot-rolled steel sheet is cooled at an average cooling rate of 20°C / s or higher. If the average cooling rate is less than 20°C / s, the transformation texture in the hot-rolled steel sheet cannot be fully developed. As a result, grains with the {100}<001> orientation, which is the primary cause of transition zone formation, develop, reducing the r-value. Furthermore, within the grains of the γ-fiber texture orientation group, the {111}<112> orientation is excessively generated, increasing the in-plane anisotropy. Therefore, the average cooling rate is set to 20°C / s or higher.
[0209] After the above cooling, at the coiling temperature T c The winding is performed within the range satisfying the following formula (a).
[0210] 580≤T c (℃)≤T+575···(a)
[0211] However, T in the above formula (a) is calculated by the following formula (b).
[0212] T=11Si+33Mn+21Mo+17(Cr+Cu+Ni)-30Al···(b)
[0213] The symbols of the elements in the above formula (b) represent the content (mass %) of the elements contained in the steel, and are set to zero when the elements are not contained.
[0214] If the coiling temperature T c If the temperature is lower than 580°C, Ti carbide precipitation does not occur during coiling, and solid solution C remains in the hot rolled steel sheet, which reduces the r value. As a result, mr may be reduced. Therefore, the coiling temperature T c On the other hand, even if the coiling temperature T cAbove T+575℃, the phase transformation texture is not fully developed, and the {100}<001> oriented grains, which are the main cause of the transition zone formation, develop, and the r value decreases. Therefore, the coiling temperature T c The temperature is set to be T+575°C or lower. After coiling, pickling may be performed as needed.
[0215] Next, cold rolling is performed to form a cold-rolled steel sheet. The rolling reduction during cold rolling (hereinafter referred to as "cold rolling rate") is set in the range of 60 to 90%. If the cold rolling rate is less than 60%, the {111} oriented grains that increase the r value are not fully developed, and the average r value decreases. Therefore, the cold rolling rate is set to 60% or more. On the other hand, if the cold rolling rate is greater than 90%, the {111}<112> oriented grains are excessively overdeveloped and the in-plane anisotropy becomes larger. Therefore, the cold rolling rate is set to 90% or less.
[0216] The resulting cold-rolled steel sheet is annealed. The annealing temperature is set at 680°C or higher. If the annealing temperature is lower than 680°C, recovery and recrystallization will not occur sufficiently, and the r-value will not increase. Furthermore, the in-plane anisotropy will increase. Therefore, the annealing temperature is set at 680°C or higher.
[0217] The holding time at the annealing temperature, i.e., the annealing time, is not particularly limited. However, for reasons of recovery and recrystallization, as well as manufacturing cost, it is typically within the range of 1 second to 10 minutes. During annealing, the annealing temperature and time are maintained at the aforementioned temperature and time. After annealing, pickling may be performed as needed.
[0218] Alternatively, the obtained steel sheet may be immersed in a galvanizing bath to form a hot-dip galvanized steel sheet having a zinc coating on the surface. Alternatively, the hot-dip galvanized steel sheet may be subjected to an alloying heat treatment to form an alloyed hot-dip galvanized steel sheet. Furthermore, the obtained steel sheet may be electroplated to form an electroplated steel sheet. Conventional methods may be used for the various plating conditions.
[0219] For example, in hot-dip galvanizing or alloyed hot-dip galvanizing, the plating composition may contain Fe, Al, Mn, Cr, Mg, Pb, Sn, Ni, etc., as required. Furthermore, the alloying heat treatment is often performed at a temperature of 450 to 600° C., and the alloying heat treatment time is often set to 10 seconds or more.
[0220] Hereinafter, the steel sheet of the present disclosure will be described in more detail using examples, but the present embodiment is not limited to these examples.
[0221] Example
[0222] Steel having the chemical composition shown in Table 1 was melted to obtain slabs. The obtained slabs were hot rolled and coiled under the conditions shown in Table 2, and then cold rolled and annealed (annealing time 60 seconds) to obtain cold-rolled steel sheets.
[0223] [Table 1]
[0224]
[0225] [Table 2]
[0226] Table 2
[0227]
[0228] * means a chemical composition that deviates from the present embodiment.
[0229] Underlined: deviates from the preferred manufacturing conditions of this embodiment.
[0230] For the obtained steel sheets and plated steel sheets, various random strength ratios (random strength ratio (A), random strength ratio (B), and random strength ratio (C)) were measured, and the ratio of random strength ratio (B) to random strength ratio (C) was calculated. Furthermore, the obtained steel sheets were subjected to tensile testing to measure tensile strength and various r values (rL, rC, and rD). The average r value and Δr were calculated from the various r values. The following describes the methods for measuring the various random strength ratios and the tensile testing method.
[0231] (Random Intensity Ratio)
[0232] Various random intensity ratios were measured in the following order. Specifically, the random intensity ratios were generated based on the crystal orientation data obtained by EBSD measurement. The degree of aggregation of each crystal orientation on the ODF of the cross section was calculated.
[0233] ODF is also used to represent the orientation of crystal structures with low symmetry, so it is generally used as Φ=0~180°、 Each orientation is represented by (hkl)[uvw]. However, in the steel plate of this embodiment, the bcc crystal structure with high symmetry is the target, so for Φ and Expressed in the range of 0 to 90°.
[0234] In addition, for The range varies depending on whether the symmetry due to deformation is considered during calculation. However, in the steel plate of this embodiment, the symmetry due to rolling deformation is considered. Mark. Figure 1 in The main orientation is shown on the ODF of the cross section. Figure 1 In the example, (111)[1-10] and (111)[0-11] are equivalent, and it is agreed that they are all {111}<110> as a mark considering symmetry. Therefore, any random intensity ratio becomes the same value, but in the steel plate of this embodiment, The value of Φ=55° is used as the random intensity ratio of {111}<110>. Similarly, {100}<001> is set as Φ=0°,{111}<112>is set to The value of Φ = 55°.
[0235] In addition, in ODF, for example, the {100}<001> orientation strictly refers to the In the cross section However, sometimes measurement errors may occur due to the processing of the test piece and the setting of the sample. The maximum value in the range of Φ = 0 to 5° represents the random intensity of the orientation. The random intensity ratio is measured with an error of ±5° allowed for each axis of Φ. Similarly, in other orientations, The measurement was performed with an error of 5° allowed for each axis of Φ.
[0236] When generating the ODF, analysis was performed under the following conditions using "OIM Analysis," which is analysis software manufactured by TSL Corporation.
[0237] Calculation method: Harmonic series expansion method
[0238] Series order [L]: 16
[0239] Gaussian half width [degrees]: 5
[0240] Sample symmetry: orthotropic (rolled steel plate)
[0241] In EBSD measurements, the steel plate is mechanically or chemically polished, and a cross section perpendicular to the plate width is polished to a mirror finish. Then, strain is removed by electrolytic or chemical polishing to produce the test specimen. The measurement range is set to the entire thickness in the plate thickness direction and 1 mm in the rolling direction. The number of measurement points is adjusted to be at least 10,000.
[0242] (Tensile test)
[0243] A tensile test was performed on the obtained steel plate, and various r values were measured. Each r value was measured by performing a tensile test in accordance with 3.1 of JIS Z 2254:2021. In addition, during the test, a strain was applied by applying a tensile elongation of 15.0±1.0% (total elongation), and after removing the strain, the length between the marks was measured. According to Note 3 of 3.1 of JIS Z 2254:2021, the r value was calculated using the formula (2) of the Note 3 using the measurement result of the length. In the tensile test, 3 test pieces were used in one direction, and the average value was set as the r value in each direction.
[0244] Test specimens were prepared in three different orientations: those with the rolling direction as the longitudinal direction, those with the longitudinal direction perpendicular to the rolling direction, and those with the longitudinal direction at a 45° angle to the rolling direction. The test specimens conformed to the JIS Z 2241:2022 No. 5 test specimen, with the distance between the markings on the parallel section set to 20 mm. A predetermined number of test specimens were collected from a predetermined distance near the center of the steel plate width where the average characteristic value was obtained, so as to avoid being affected by processing during collection.
[0245] Furthermore, a No. 5 test piece of JIS Z 2241:2022 was prepared so that the rolling direction was the longitudinal direction, which was different from the above, and a tensile test was performed until it broke to measure the tensile strength (TS).
[0246] [Table 3]
[0247]
[0248] * means departure from the requirements of this embodiment.
[0249] Nos. 1, 3, 5, 7, 9, 11, 14, 16, 18, 20, 22, 24, 26, and 27, which satisfy the requirements of this embodiment, exhibit good deep drawability. On the other hand, Nos. 2, 4, 6, 8, 10, 12, 13, 15, 17, 19, 21, 23, 25, 28, and 29, which do not satisfy this embodiment, have reduced at least one of the various r values, average r value, and Δr, and do not exhibit good deep drawability.
Claims
1. A cold-rolled steel sheet having a chemical composition of C: 0.0005-0.0070% by mass, Si: 0.01-1.50%, Mn: 0.05-1.50%, P:0.001~0.150%、 S:0.0005~0.0100%、 Al:0.005~0.100%、 N:0.0010~0.0200%、 Ti: 0.010~0.150%, Sn: 0.020~0.080%, Nb: 0~0.060%, B:0~0.0030%、 Mo: 0~0.50%, Cr:0~3.00%、 W:0~3.00%、 Cu: 0-3.00%, Ni: 0-3.00%, Ca: 0~0.1000%, REM: 0~0.100% V:0~0.10%、 As: 0~0.10%, Sb: 0-0.10%, Pb: 0~0.10%, Bi: 0~0.10%, Balance: Fe and impurities, The cold-rolled steel sheet satisfies the following equations (i) and (ii): rL, which is the r value in the rolling direction, is 1.50 or more. rC, which is the r value in the direction perpendicular to the rolling direction, is 1.50 or more. rD, which is the r value in the direction at 45° to the rolling direction, is 1.50 or more. mr defined by the following formula (iii) is 1.70 or more, Δr defined by the following formula (iv) is in the range of -0.40 to 0.40, Ti-48 / 32×S-48 / 14×N-48 / 12×C≥-0.010···(i), 5.0≤11Si+33Mn+21Mo+17(Cr+Cu+Ni)-30Al≤50.0···(ii), mr=(rL+2rD+rC) / 4···(iii), Δr=(rL+rC-2rD) / 2···(iv), in, The symbols of the elements in the above formulae (i) and (ii) represent the mass % content of the elements contained in the steel, and when the elements are not contained, the content is set to 0%.
2. The cold-rolled steel sheet according to claim 1, wherein: In the cold-rolled steel sheet, The random intensity ratio (A) which is the random intensity ratio of the {100}<001> orientation is 1.8 or less, The random intensity ratio (B), which is the random intensity ratio of the {111}<112> orientation, is 4.0 or more, The random intensity ratio (C), which is the random intensity ratio of the {111}<110> orientation, is 4.0 or more, The ratio of the random intensity ratio (B) to the random intensity ratio (C) satisfies the following formula (v): 0.80≤random intensity ratio (B) / random intensity ratio (C)≤1.20···(v).
3. The cold-rolled steel sheet according to claim 1 or 2, wherein: The chemical composition contains, in mass%, Nb: 0.001~0.060%, B:0.0001~0.0030%、 Mo: 0.01~0.50%, Cr:0.01~3.00%、 W:0.01~3.00%、 Cu: 0.01~3.00%, Ni: 0.01~3.00%, Ca: 0.0001~0.1000%, REM: 0.001~0.100%, V: 0.01~0.10%, One or more of As: 0.01 to 0.10%, Sb: 0.01 to 0.10%, Pb: 0.01 to 0.10%, and Bi: 0.01 to 0.10%.
Citation Information
Patent Citations
High-strength cold-rolled steel sheet excellent in deep drawability and method for producing the same
JP2006219737A
Cold rolled steel sheet having excellent deep drawability and method for producing the same
JP2009270191A